Following of Protocols for the Blood Transfusion: An Audit Report - Ali, Sara; Riaz, Faiqa; Arshad, Inshal; Anjum, Zohaib; Nisha (Indus Journal of Bioscience Research, 2025)
Background: Blood transfusion is a vital medical procedure widely used in clinical practice. However, non-adherence to established transfusion protocols can result in preventable errors, patient harm, and increased healthcare costs. In resource-constrained public hospitals, protocol compliance is often compromised due to workforce limitations and system inefficiencies. Objective: This audit was conducted to assess adherence to standardized blood transfusion protocols among physicians in the Department of Medicine at Gujranwala Medical College Teaching Hospital and to evaluate the impact of targeted intervention on improving compliance. Methods: A one-week clinical audit was conducted in January 2024. A total of 15 transfusion procedures were observed using a structured audit proforma based on Joint United Kingdom Blood Transfusion and Tissue Transplantation Services Professional Advisory Committee (JPAC) guidelines. Key parameters such as documentation, consent, identity verification, vital sign monitoring, and self-safety practices were assessed. After an initial audit, a departmental training session was conducted, followed by a re-audit two weeks later using the same criteria. Results: Pre-intervention audit results revealed a compliance rate of 58.5%. The lowest adherence was noted in documentation and pre-transfusion vital monitoring. Following the intervention, compliance significantly improved to 70.4%, with notable gains in documentation, consent, and proforma usage. Conclusion: The audit demonstrates substantial gaps in protocol adherence but also highlights the positive impact of low-cost, department-led educational interventions. Regular audits, staff training, and procedural reinforcement can significantly enhance transfusion safety and patient care quality.